Wear Behavior of Aluminium Metal Matrix Composite Prepared from Industrial Waste - L. Francis Xavier; Paramasivam Suresh (The Scientific World Journal)
With an increase in the population and industrialization, a lot of valuable natural resources are depleted to prepare and manufacture products. However industrialization on the other hand has waste disposal issues, causing dust and environmental pollution. In this work, Aluminium Metal Matrix Composite is prepared by reinforcing 10 wt% and 20 wt% of wet grinder stone dust particles an industrial waste obtained during processing of quarry rocks which are available in nature. In the composite materials design wear is a very important criterion requiring consideration which ensures the materials reliability in applications where they come in contact with the environment and other surfaces. Dry sliding wear test was carried out using pin-on-disc apparatus on the prepared composites. The results reveal that increasing the reinforcement content from 10 wt% to 20 wt% increases the resistance to wear rate.